A Novel Tourniquet with an Alarm System, Replaceable Components, and The Ability to Adjust Pressure and Detect Body Temperature for Medical Applications - Bameri, Mohammad Mahdi; Abolhassani, Moussa; Bameri, Mohammad Hasan; Shafaghi, Shadi; Ghorbani, Fariba; Shafaghi, Masoud (Department of Electromedical Engineering, POLTEKKES KEMENKES SURABAYA, 2023)
A tourniquet is a practical device in the medical field that is employed to collect blood and prevent bleeding in medical centers. The need for a durable tourniquet with leveled pressure adjustment capabilities, which indicates the time, can be used for both blood collection and control of intense bleeding, and has replaceable components in case of damage is strongly felt. Thus, developing a tourniquet with the aforementioned features is highly beneficial. The designed tourniquet includes four main parts (end hook, strap, main clip, and pin), and the other three parts are mounted on the strap. This tourniquet has a unique strap design and a sturdy lock and fastener, a body temperature detection sensor, a pressure adjustment section at four levels, a timer with an alarm, buttons (pins) to open the strap, a linen pad, and a special end hook (with an end clamp). The proposed time warning tourniquet with replaceable components has the ability to adjust the pressure, detect the temperature, and create local pressure, and therefore, can boost the performance of the medical staff during blood sampling and bleeding control procedures.